2007
DOI: 10.1017/s1751731107000730
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants for helminth parasite control: facts and fiction

Abstract: The use of medicinal plants for the prevention and treatment of gastro-intestinal parasitism has its origin in ethnoveterinary medicine. Although until recently the majority of the evidence on the antiparasitic activity of medicinal plants was anecdotal and lacked scientific validity, there is currently an increasing number of controlled experimental studies that aim to verify and quantify such plant activity. There are indeed a large number of plants whose anthelmintic activity has been demonstrated under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
136
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 66 publications
1
136
1
8
Order By: Relevance
“…The imperative to identify alternatives to drugs for control of parasites is apparent in the areas targeted by the Enrich project which show widespread resistance to existing anthelmintic drugs (Besier and Love, 2003). There is extensive literature on the use of plants to provide an anthelmintic component to the diet of grazing livestock (reviewed by Athanasiadou and Kyriazakis, 2004 ;Hoste et al 2006 ;Athanasiadou et al 2007) ; however, there has been no study in the past of the potential role of Australian native shrub species in this regard. The present study was therefore initiated to use in vitro bioassays to identify shrub species that possess significant anthelmintic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The imperative to identify alternatives to drugs for control of parasites is apparent in the areas targeted by the Enrich project which show widespread resistance to existing anthelmintic drugs (Besier and Love, 2003). There is extensive literature on the use of plants to provide an anthelmintic component to the diet of grazing livestock (reviewed by Athanasiadou and Kyriazakis, 2004 ;Hoste et al 2006 ;Athanasiadou et al 2007) ; however, there has been no study in the past of the potential role of Australian native shrub species in this regard. The present study was therefore initiated to use in vitro bioassays to identify shrub species that possess significant anthelmintic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the trial conducted by Luginbuhl et al (2006), another commercially available herbal de-wormer was ineffective in reducing EPG counts in goats, and in the study by Bouilhol et al (2001) there were no apparent anti-parasitic effects of fi ve different herbal preparations on gastrointestinal helminths in grazing sheep. Contrary to the aforementioned fi eld studies, a number of in vivo and in vitro experiments have been supportive of the effi cacy of using plant extracts for the control of gastrointestinal parasites, especially the nematodes, in small ruminants (Githiori et al, 2006;Athanasiadou et al, 2007) and others reported inconsistent outcomes (Torres-Acosta & Hoste, 2008). A high dose of A. sativum extracts -one of the plants used in the preparation of mineral licks tested in the present trial -reduced the nematodes' EPGs in sheep (Masamba et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It is, therefore, feasible that the doses of extracts used by the manufacturer of the Star Bloc Phyto Vers mineral supplements are not high enough to produce therapeutic or anti-parasitic effects. On the other hand, continual oral administration of the larger amounts of some herbal extracts contained in this product could be harmful to animals because of their potential toxicity and hence relatively narrow ranges of therapeutic doses (Waller et al, 2001;Athanasiadou et al, 2007). In sheep with the mixed nematode infections and presence of blood-suckling species such as H. contortus or T. circumcincta the estimated threshold levels for helminthiases are 50 -800 EPGs for light, 800 -1200 EPGs for moderate, and >1200 EPGs for heavy infections (Hansen & Perry, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations